Actinomycosis of the Appendix Mimicking Cecal Tumor Treated by Single-Port Laparoscopic Approach - Cho, In Soo; Bae, Sung Uk; Jung, Hye Ra; Park, Kyung Sik; Jeong, Woon Kyung; Baek, Seong Kyu (Annals of coloproctology, 2021)
Actinomycosis is an inflammatory disease with various clinical presentations including inflammation and formation of masses. There are several reports suggesting the infiltrative mass-like nature of actinomycosis that is misunderstood as a tumor. A 39-year-old male clinically presented with a fungating mass-like lesion during colonoscopy for healthcare screening. Biopsy was performed for the lesion, and chronic inflammation was diagnosed. Abdominal computed tomography (CT) suggested severe edematous changes in the appendix with an appendicolith, suspected chronic inflammation, and wall thickening of the cecal base, but malignancy could not be definitively ruled out. The patient underwent a laparoscopic single-port cecectomy based on the possibility of cecal cancer. The final biopsy was diagnosed as actinomycosis, and the patient was prescribed antibiotics and showed no recurrence in the follow-up CT scan. We present this rare case of mass-like appendiceal actinomycosis treated with the single-port laparoscopic method.